2016
DOI: 10.1016/j.resp.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in oropharyngeal sensory evoked potentials (PSEP) with Parkinson’s disease

Abstract: Movement of a food bolus from the oral cavity into the oropharynx activates pharyngeal sensory mechanoreceptors. Using electroencephalography, somatosensory cortical-evoked potentials resulting from oropharyngeal mechanical stimulation (PSEP) have been studied in young healthy individuals. However, limited information is known about changes in processing of oropharyngeal afferent signals with Parkinson’s disease (PD). To determine if sensory changes occurred with a mechanical stimulus (air-puff) to the orophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…For example, Baille et al (2019a) recently demonstrated high levels of dyspnea in patients with Parkinson’s disease, which was related to higher levels of depression and anxiety ( Baille et al, 2019a ). It may be suspected that these associations are related to disturbed emotional modulations of the neural respiratory sensory gating mechanism, which is further supported by previous findings showing abnormal sensory gating patterns for oropharyngeal stimuli in patients with Parkinson’s disease ( Pitts et al, 2016 ). If found to be true, such disturbances in the interrelationships between emotions and respiratory sensory gating may offer a target for therapeutic interventions in these patients.…”
Section: Discussionsupporting
confidence: 73%
“…For example, Baille et al (2019a) recently demonstrated high levels of dyspnea in patients with Parkinson’s disease, which was related to higher levels of depression and anxiety ( Baille et al, 2019a ). It may be suspected that these associations are related to disturbed emotional modulations of the neural respiratory sensory gating mechanism, which is further supported by previous findings showing abnormal sensory gating patterns for oropharyngeal stimuli in patients with Parkinson’s disease ( Pitts et al, 2016 ). If found to be true, such disturbances in the interrelationships between emotions and respiratory sensory gating may offer a target for therapeutic interventions in these patients.…”
Section: Discussionsupporting
confidence: 73%
“…Although delay of earlier pSEP peaks (N1/P1) is probably related to conduction slowing through the afferent pathway at the stroke site, delay of later peaks (N2/P2) also suggests impaired integration of sensory inputs. ERP studies have reported an altered pharyngeal sensory pathway in dysphagic elderly people and in Parkinson's disease [6,19]. The inverse correlation that we found between N2/P2 amplitude and LV closure time indicates that impaired sensory integration of pharyngeal inputs is associated with impaired safety of swallowing.…”
Section: Pharyngeal Sensory Pathwaymentioning
confidence: 47%
“…Mu and Sanders found aggregates of alpha‐synuclein protein in the sensory nerve terminals of people with PD premortem, suggesting that possibly the initial sensory stimulus is inadequately transduced to sensory afferents . Another possibility is that there is over‐gating of sensory information by the thalamus, whereby the thalamus inhibits throughput of sensory signals to the primary sensory cortex . Indeed, changes in sensory processing of both discriminative and affective components of a sensory stimulus could contribute to these findings, as the neuropathology of PD is known to extend beyond the basal ganglia .…”
Section: Discussionmentioning
confidence: 99%